Schizophrenia, Bipolar Disorder and Pre-Attentional Inhibitory Deficits - Vlcek, Premysl; Bob, Petr (Neuropsychiatric disease and treatment, 2022)
According to recent findings schizophrenia and bipolar disorder as separate disease entities manifest similarities in neuropsychological functioning. Typical disturbances in both disorders are related to sensory gating deficits characterized by decreased inhibitory functions in responses to various insignificant perceptual signals which are experimentally tested by event related potentials (ERP) and measured P50 wave. In this context, recent findings implicate that disrupted binding and disintegration of consciousness in schizophrenia and bipolar disorder that are related to inhibitory deficits reflected in P50 response may explain similarities in psychotic disturbances in both disorders. With this aim, this review summarizes literature about P50 in both schizophrenia and bipolar disorder.
Keywords: event related potentials; P50; inhibition; schizophrenia; bipolar disorder; neural synchrony